Internet Usage and Ideal Number of Children in Indonesia (The Analysis of The 2017 IDHS) - Yasmin Fitriana Imanuddin (AFEBI Economic and Finance Review, 2021)
Internet usage in Indonesia is growing rapidly each year. Information on the internet is considered to affect the way of thinking and the behaviour of its users. This can be seen, among other things, on the women internet user’s desired or ideal number of children. This research aims to study the patterns and differentials of the ideal number of children among women in Indonesia according to internet usage and the effect of the use of internet on women’s ideal number of children in Indonesia after controlling for the effects of socio-economic factors. This study used data from the results of 2017 Indonesia Demographic and Health Survey (DHS). The method used to analyze the data is multinomial logistic regression. The analysis is conducted on all childbearing-aged women (15-49 years old) and married childbearing-aged women. The results of the study show that childbearing-aged women who used the internet wanted less children compared to those who did not use the internet. The results of this study can be used as a reference by the related stakeholders to formulate policies that support fertility level management in Indonesia using information and communication technology, the internet in particular.